How Do Santri, Local Wisdom, and Digital Transformation Affect Community Empowerment? - Aang Kunaifi; Khusnul Fikriyah; Dewi Aliyah (Ilomata International Journal of Social Science, 2021)
Santri is an unique person in a various economic activities. In the mix of local wisdom that is thick with spiritual values and wrapped in the dynamics of the use of digital technology, students are seen as having a real influence in realizing community empowerment in the economic field. This article aims to describe the role of santri through local wisdom and the use of digital technology in creating community empowerment. To get accurate and up-to-date information, observations and collect information has done by interviewed to santri about their strategies in dealing with economic problems in the regency as well as tips on utilizing digital technology. Furthermore, the information is checked with primary sources in the form of community members to measure the effectiveness of the role of the santri. The analysis and discussion of the data was carried out qualitatively with the phenomenological approach of the Madurese community. The research findings in this article show that there is a collaboration of the attitude and mentality of students in the midst of society with personal capital of independence, honesty, and work ethic. In terms of using digital technology, they are also able to adapt quickly and precisely. Thus, this research is expected to be able to provide a complete and accurate description of the existence and role of santri in creating community empowerment in the economic field, so that regulatory and policymakers can determine priorities in regional and national development.